Maladaptive behaviours of maternal orphans in high schools of Tshwane North of Gauteng, South Africa - Thembi V. Khoza; Mathildah M. Mokgatle (AOSIS, 2023)
Background: Some orphaned adolescents find it difficult to cope and adjust to the loss of a mother. Studies to explore specific adjustment challenges experienced by this vulnerable group, are necessitated by the growing need to inform support services for orphans. Aim: This study sought to explore maladaptive behaviours among adolescent maternal orphans. Setting: Participants were recruited from the Tshwane North secondary schools of Gauteng province in South Africa. Methods: A qualitative exploratory design was employed; maternal adolescent orphans were purposively selected and included in a one-on-one qualitative enquiry. Twenty-five participants were included in the study. Data were analysed thematically using NVivo12. Results: Emerged themes were: negative thoughts such as suicidal ideation, negative perception of self; silence coded as 'keep life matters private and hide personal feelings'; having psychosocial problems reported as anger, fighting, shouting, crying, short temper; engaging in risky behaviours in the form of smoking and alcohol use and unsafe termination of pregnancy; social withdrawal by self-isolation and being afraid of people. Conclusion: Whole school peer interaction groups could address the functional problems of social ability and silence. Skills development programmes, and other activities that enhance constructive use of free time, instil hope and build self-esteem are recommended. Contribution: The findings of this study serve as a basis to inform interventions that are geared towards supporting adolescent orphans through the school health teams, as one of the domains of the re-engineering of South Africa's primary health care system.